2016
DOI: 10.1016/j.athoracsur.2015.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Core Muscle Size Predicts Postoperative Outcome in Lung Transplant Candidates

Abstract: LPA can easily be assessed in LT candidates as part of pretransplant evaluation and was significantly associated with short-term outcome, whereas BMI was not. Assessment of LPA may provide additional information on body composition beyond BMI. However, the clinical utility has to be further evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 28 publications
3
82
3
Order By: Relevance
“…Genetic susceptibility, comorbidities, physiological aging, and environmental factors, also play a role in the pathophysiology of frailty. [7][8][9][10][11] Sarcopenia and frailty share similar underlying mechanisms, such as physical inactivity, chronic inflammation, and endocrine dysregulation. 2 Biomarkers for frailty have been suggested, based on the concept that aging represents a low-grade chronic inflammatory process, sometimes termed "inflammaging."…”
Section: Pathophys Iology Of Fr Ailt Ymentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic susceptibility, comorbidities, physiological aging, and environmental factors, also play a role in the pathophysiology of frailty. [7][8][9][10][11] Sarcopenia and frailty share similar underlying mechanisms, such as physical inactivity, chronic inflammation, and endocrine dysregulation. 2 Biomarkers for frailty have been suggested, based on the concept that aging represents a low-grade chronic inflammatory process, sometimes termed "inflammaging."…”
Section: Pathophys Iology Of Fr Ailt Ymentioning
confidence: 99%
“…2 Biomarkers for frailty have been suggested, based on the concept that aging represents a low-grade chronic inflammatory process, sometimes termed "inflammaging." 13 Sarcopenia, like frailty, may be a risk factor for worse outcomes in lung transplant candidates; however, data are conflicting, with some studies showing lower pretransplant skeletal muscle mass measured radiographically being a risk factor for worse outcomes, 9,14 and others showing risk for longer hospital stays but not mortality. [3][4][5] Sarcopenia (loss of skeletal muscle mass) may be a precursor to the development of frailty and its adverse health outcomes.…”
Section: Pathophys Iology Of Fr Ailt Ymentioning
confidence: 99%
“…Therefore, in nonobese waitlisted ILD patients, reducing body fat mass by nutritional intervention cannot be recommended because it may instead decrease TTR and albumin and possibly promote sarcopenia, 30,31 which results in poor prognosis. The relationship between body fat mass and TTR has not been reported in ILD.…”
Section: Discussionmentioning
confidence: 99%
“…Our results further support the usefulness of PR even in patients with end-stage lung disease. This is of particular interest for patients awaiting lung transplantation, since pretransplant functional status is closely related to transplant outcome [3]. Large studies of the UNOS database have shown that pretransplant 6MWD is a significant predictor of waitlist mortality [26] and is significantly associated with posttransplant survival [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Interest in the benefits of PR in patients with end-stage lung disease awaiting lung transplantation is increasing, since maintenance of exercise capacity and muscle mass are critical for survival on the waiting list and for transplant outcome [3-5]. …”
Section: Introductionmentioning
confidence: 99%